Oncocytic Change in Thyroid Pathology - Asa, Sylvia L.; Mete, Ozgur (Frontiers in Endocrinology, 2021)
Oncocytes are cells that have abundant eosinophilic cytoplasm due to the accumulation of mitochondria; they are also known as oxyphils. In the thyroid they have been called Hürthle cells but this is a misnomer, since Hürthle described C cells; for this reason, we propose the use of “oncocyte” as a scientific term rather than an incorrect eponym. Oncocytic change occurs in nontumorous thyroid disorders, in benign and malignant tumors of thyroid follicular cells, in tumors composed of thyroid C cells, and intrathyroidal parathyroid proliferations as well as in metastatic lesions. The morphology of primary oncocytic thyroid tumors is similar to that of their non-oncocytic counterparts but also is complicated by the cytologic features of these cells that include both abundant eosinophilic cytoplasm and large cherry red nucleoli. The molecular alterations in oncocytic thyroid tumors echo those of their non-oncocytic counterparts but in addition feature mitochondrial DNA mutations as well as chromosomal gains and losses. In this review we emphasize the importance of recognition of the spectrum of oncocytic thyroid pathology. The cell of origin, morphologic features including architecture, nuclear atypia and invasive growth, as well as high grade features such as mitoses and necrosis, enable accurate classification of these lesions. The molecular alterations underlying the pathological entity are associated with genetic alterations associated with oncocytic change. The arbitrary cut-off of 75% oncocytic change to classify a lesion as an oncocytic variant brings another complexity to the classification scheme of tumors that frequently have mixed oncocytic and non-oncocytic components. This controversial and often confusing area of thyroid pathology requires thoughtful and cautious investigation to clarify accurate diagnosis, prognosis and prediction for patients with oncocytic thyroid lesions.